Abnormal Uterine Bleeding in Adolescence: When Menarche Reveals other Surprises - Helena Gomes; Bruna Abreu; Liliana Barros; Carlos Veríssimo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Introduction Abnormal uterine bleeding is more frequent in adolescence. Although, most commonly, it has a non-structural etiology, it may be due to any cause described. Clinical case A 12-year-old adolescent, with no relevant personal history, menarche 1 month before, was observed in the emergency department for severemenstrual bleeding with progressive worsening, and hemodynamic repercussion in need of transfusion support. Physiological ovulatory dysfunction associated with possible previously unknown coagulopathy was considered to be the most likely diagnosis and medical treatment was initiated. Without response, the patient was submitted to sedated observation and uterine aspiration, which ultimately led to the diagnosis of a Burkitt Lymphoma. Discussion Although structural causes, and particularly malignancy, whether gynecological or not, are a rare cause of abnormal uterine bleeding in this age group, they must be considered, thus enhancing the fastest and most appropriate treatment.